Steve Jobs : insanely great - Hartland, Jessie (Schwartz & Wade Books, 2015)
This biography in graphic format presents the story of the ultimateAmerican entrepreneur, who brought us Apple Computer, Pixar, Macs, iPods, iPhones and more, this unique and stylish book is sure to appeal to the legions of readers who live and breathe the techno-centric world Jobs created.